Utilization of cotton byproduct-derived biochar: A review on soil remediation and carbon sequestration - Tao, Yingru; Feng, Weiying; He, Zhongqi; Wang, Beibei; Yang, Fang; Aainaa Izyan, Nafsun; Zhang, Yazhai (Springer, 2024)
Biochar can improve soil health and fix CO2 by altering soil microenvironment, thus impacting the global carbon cycle and the change of soil ecological environment. Recent studies show that cotton byproduct-derived biochar is a potential effective amendment for soil improvement so that it could play an important role in agricultural and environmental conservation. In this work, research topics on cotton byproduct-derived biochar in soil in last decade and so are systematically reviewed for better understanding of the progresses of cotton byproduct-derived biochar in (i) the morphologic and physicochemical characterization, (ii) latest research hotspots and trends, (iii) the roles in soil reclamation, and (iv) relevant carbon sequestration mechanisms. Finally, the future research directions regarding cotton byproduct-derived biochar mingled to soil environment are discussed. Insight derived from this work would provide scientific basis for promoting more applications of cotton byproduct-derived biochar in soil ecological restoration and carbon fixation.